Fabrication of novel Ti1.1V1.1Cr0.4Nb1.4C3Tx medium-entropy MXene through the thermodynamic competition strategy - Tan, Chaowen; Ma, Wansen; Hu, Liwen; Li, Qian; Lv, Xuewei; Dang, Jie (Acta materialia, 2024)
As a new type of two-dimensional material, MXenes with increased entropy (ME/HE-MXenes) possess immense potential for exhibiting unforeseen properties, making them a compelling subject for further investigation. However, due to the difficulty in predicting and preparing stable medium-entropy MAX (ME-MAX), as precursors of ME-MXenes, only a few ME-MXenes have been synthesized successfully. Herein, we proposed a thermodynamic competition strategy that enabled the successful synthesis of a stable ME-MAX consisting of four-transition metals: Ti, V, Cr and Nb, which was first predicted by density functional theory calculation. The resulting ME-MAX with a hexagonal crystal structure and pseudo-structure of P63/mmc, possessed the chemical formula TiVCrNbAlC3. Subsequently, the corresponding ME-MXene was prepared by selectively etching the Al layer using HF acid, obtaining the desired composition of Ti1.1V1.1Cr0.4Nb1.4C3Tx. Furthermore, aberration-corrected scanning transmission electron microscopy analysis revealed that the MX slabs within the prepared ME-MXene contained four transition metal layers arranged in an α-configuration, which was consistent with the atomic structure of the ME-MAX. In comparison to single transition metal MXenes, the tailored ME-MXene showcased lattice distortions attributable to the highly diverse composition space, consequently leading to increased active sites and improved electrical conductivity. As a result, the annealed Ti1.1V1.1Cr0.4Nb1.4C3Tx has higher mass capacitances when used as the supercapacitor negative electrode, with weight capacitances of 292.74 F g−1 at 2 mV s−1 and 137.20 F g−1 at 200 mV s−1. The strategy proposed in this study not only expands the realm of achievable ME-MAX compositions but also opens up new possibilities for derivative medium-entropy MXenes. We reported thermodynamically competitive strategy for the synthesis of TiVCrNbAlC3 ME-MAX, which was subsequently etched to obtain Ti1.1V1.1Cr0.4Nb1.4C3Tx ME-MXene. As determined by AC-STEM, the MX slabs within the synthesized ME-MXene contained four transition metal layers arranged in an α-configuration. Remarkably, when employed as the negative electrode in a supercapacitor, the ME-MXene demonstrated a higher weight capacitance of 292.74 F g−1 at 2 mV s−1, surpassing the performance of STM MXenes prepared using the same methodology. [Display omitted]